Developing Preservice Chemistry Teachers’ Engagement with Sustainability Education through an Online Project-Based Learning Summer Course Program - Paristiowati, Maria; Rahmawati, Yuli; Fitriani, Ella; Satrio, Justinus A.; Putri Hasibuan, Nur Azizah (Sustainability, 2022)
The aim of this research was to develop the sustainability competencies of preservice chemistry teachers’ through the use of a project-based learning model. Preservice chemistry teachers were engaged in a summer course program in collaboration with national and international universities. The summer course program was conducted online due to the COVID-19 pandemic. The research involved 26 preservice chemistry teachers from a pedagogical university in Jakarta, Indonesia, which joined with other university students from other universities in Indonesia, America, Thailand, and Malaysia. We used a qualitative methodology. Data were collected through interviews, questionnaires, observations, preservice chemistry teachers’ portfolios, and reflective journals. The data were coded into themes and interpreted to reveal that all students engaged successfully in developing their sustainability perspectives, environmental awareness, project development engagement, communication, and collaboration skills. Meanwhile, the preservice chemistry teachers engaged in developing their project in an online summer course program within the framework of sustainability.